Analisis Pengelolaan Limbah Industri Tahu dan Potensi Dampaknya terhadap Lingkungan Sekitar di Desa Tawangsari - Nonaqu Beautyla Putri Dharmawan; Nur Qoilun (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
This study aims to analyze the management of tofu industry waste and its environmental impacts from the perspective of environmental law. The research was conducted at Pabrik Tahu Barokah Jaya, located in Tawangsari Village, Taman District, Sidoarjo Regency, using a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model. The results show that solid waste has been reused, while liquid waste is still discharged directly without treatment, causing environmental impacts such as water discoloration, unpleasant odors, and decreased water quality. Legally, this condition is not fully in accordance with Law Number 32 of 2009 concerning Environmental Protection and Management.